Sentenced to Pretrial Detention: A Study of Bail Decisions and Outcomes - Sacks, Meghan (American journal of criminal justice, 2015)
Previous research on bail practices has shown that both legal factors, such as offense severity and prior criminal record, and demographic factors such as race and age, exert a strong influence on bail decisions and outcomes. Using a novel application of Knowledge Discovery statistical methods, Bayesian probability analytics, this study utilized a sample of ( n = 975) cases collected by New Jersey’s Criminal Disposition Commission, followed from arrest through disposition, to examine bail decisions made by judges and subsequent bail outcomes, i.e., whether defendant was able to meet financial bail requirements to secure release from jail. We found the following: Black and Hispanic defendants are more likely than their white counterparts to have to pay a financial bail requirement; modest differences between races with regards to bail amount set by the court; and that minority defendants, and especially Hispanic defendants, are at a disadvantage when it comes to being able to post bail and they are therefore much more likely than their white counterparts to be held in pretrial detention.